Effect of different drying methods on the sensory quality and chemical components of black tea. (January 2019) - Qu, Fengfeng; Zhu, Xiaojing; Ai, Zeyi; Ai, Yujie; Qiu, Fangfang; Ni, Dejiang
Abstract: This study investigated the effects of conventional hot-air drying, microwave drying, far-infrared drying, halogen lamp drying and halogen lamp-microwave combination drying on sensory and chemical quality of black tea. Sensory evaluation revealed that the black tea dried with halogen lamp-microwave and microwave got more uniform black color, fresher taste and higher sweet aroma. Total quality score was in the order: halogen lamp-microwave dried tea (89.3) > microwave dried tea (88.2) > halogen lamp dried tea (86.4) > far-infrared dried tea (85.2) > hot-air dried tea (83.1). The highest contents of polyphenols, catechins and theaflavins were found when black tea dried with microwave. Far-infrared drying and hot-air drying could remarkably increase the contents of amino acids and soluble sugars. The volatiles of black tea were identified with gas chromatography-mass spectrometry. Microwave dried black tea got the maximum contents of volatile compounds, followed by halogen lamp-microwave dried tea, far-infrared dried tea, halogen lamp dried tea and hot-air dried tea. Overall, microwave drying and halogen lamp-microwave drying could ameliorate the drying process of black tea. Highlights: Halogen-lamp-microwave dried tea got best sensory quality. Microwave dried tea had higher polyphenols, theaflavins but lower amino acids. Microwave and halogen-lamp-microwave dried tea got new aroma compounds. Microwave and halogen-lamp-microwave drying are more suitable for black tea drying.